Conserving focal insect groups in woodland remnants: The role of landscape context and habitat structure on cross-taxonomic congruence. (August 2020) - Yong, Ding Li; Barton, Philip S.; Okada, Sachiko; Crane, Mason; Cunningham, Saul A.; Lindenmayer, David B.
Highlights: Wild bees and ground-dwelling beetles are sampled in remnant woodlands in Australian agriculture landscape. Beetle diversity more strongly shaped by differing landscape contexts than bee diversity. Species composition of both groups responds more strongly to the landscape than species richness. Bee and beetle assemblages are poor surrogates for each other in modified landscapes. Landscapes managed to conserve bees should not be assumed to benefit other insect groups. Abstract: Determining the shared responses of different taxa to landscape modification is a key step for identifying which groups of species are good surrogates for other groups. Yet, surprisingly little is known about the spatial processes that drive cross-taxonomic congruence of diversity and how this knowledge can be used to improve the management of modified landscapes for biodiversity, especially insects. We investigated how assemblages of two ecologically important insect groups, wild bees and beetles, respond to different landscape contexts and habitat structure in an Australian agricultural landscape, and how this, in turn, influenced either group's potential as a surrogate for the other. Bee and ground-active beetle assemblages were sampled in remnant woodland patches in two landscape contexts: woodland patches surrounded by pine plantation and woodland patches surrounded by open grazing land. Bee species richness, and the richness of functionally-defined bee groups did not differ between landscape contexts, in contrast to beetles. We found that landscape context exerted a stronger effect on species composition than species richness of both groups. Although some landscape and habitat variables were useful in predicting the diversity of both insect groups, few were shared. Our findings showed that bee and beetles are poor surrogates for each other in landscapes that are highly modified. Our study highlighted the need to consider: (1) taxon-specific responses to landscape context, (2) the influence of different metrics of cross-taxonomic surrogacy and, (3) dissimilar ecological attributes among insect taxa when selecting insects as biodiversity surrogates. It should not be assumed that agricultural landscapes managed to conserve specific insects (e.g. bees) will necessarily benefit other insects.